2022
DOI: 10.1083/jcb.202201094
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor BAP1 nuclear import is governed by transportin-1

Abstract: Subcellular localization of the deubiquitinating enzyme BAP1 is deterministic for its tumor suppressor activity. While the monoubiquitination of BAP1 by an atypical E2/E3-conjugated enzyme UBE2O and BAP1 auto-deubiquitination are known to regulate its nuclear localization, the molecular mechanism by which BAP1 is imported into the nucleus has remained elusive. Here, we demonstrated that transportin-1 (TNPO1, also known as Karyopherin β2 or Kapβ2) targets an atypical C-terminal proline-tyrosine nuclear localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Similar to what is observed in TP53 germline mutations in the Li-Fraumeni syndrome, BAP1 germline mutations are inherited as autosomal-dominant mutations with high penetrance, since more than 80% of carriers are destined to develop at least one of the main BAP1 -associated malignancies throughout their life. Of note, the genomic analysis of BAP1 -related tumors has highlighted the loss of the remaining BAP1 wild-type allele, something that suggests the possible role as “two-hits” tumor suppressor gene by BAP1 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to what is observed in TP53 germline mutations in the Li-Fraumeni syndrome, BAP1 germline mutations are inherited as autosomal-dominant mutations with high penetrance, since more than 80% of carriers are destined to develop at least one of the main BAP1 -associated malignancies throughout their life. Of note, the genomic analysis of BAP1 -related tumors has highlighted the loss of the remaining BAP1 wild-type allele, something that suggests the possible role as “two-hits” tumor suppressor gene by BAP1 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…BAP1 is regulated by ubiquitination through the E2 ubiquitin-conjugating enzyme UBE2O, which results in its sequestration in the cytoplasm [ 71 ]. This is counteracted through TNPO1 binding [ 72 ]. Moreover, cBAP1 is reported to regulate processes via its cytoplasmic fraction, such as apoptosis via modulation of IP3R3-mediated ER Ca 2+ release [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…83 Furthermore, TNPO1 imports the Wnt signaling effector β-catenin as well as the tumor suppressor BAP1, and many viruses exploit TNPO1 for nuclear entry and replication. [104][105][106][107] Proteome analysis indicated that proteins related to nuclear division and tRNA ligases are preferentially cargoes of TNPO1, while proteins related to DNA repair and HMG proteins are preferentially imported by TNPO2. 88 Interestingly, TNPO2 enhances export of a large proportion of mRNAs through the formation of a complex with RanGTP and the mRNA export factor NXF1, 108 suggesting that it may be appropriate to classify TNPO2 as a biportin.…”
Section: Components Of the Nuclear Transport Systemmentioning
confidence: 99%